Discovering the coping strategies of speaking anxiety in english language amongESL Learners/ Siti Nurfirdaus Mohd Nasir...[et al.] - Mohd Nasir, Siti Nurfirdaus; Harun, Nur Hartini; Harun, Zetty Harisha; Harun, Robekhah (2019)
This study intended to identify the most common strategy used by ESL learners in order to cope with speaking anxiety and also to determine any differences in the strategies used to cope with speaking anxiety between genders. A set of questionnaire was distributed to 40 students to identify the most common strategy used to help them reduce their language anxiety in speaking English and to determine any differences in the strategies used by gender. The descriptive analysis showed the highest percentage on the students working collaboratively in small groups helps to reduce their nervousness when speaking English for both gender (100%). However, the least chosen strategies are different for both genders, whereby, for female, the item ‘accuracy is not the focus and to be able to use English in a friendly environment’ respectively showed 75%, meanwhile 85% of male students agreed that ‘a humorous teacher helps to reduce nervousness in speaking English’. Finally, from the study, there are several actions that can be taken by the researchers in order to overcome language anxiety by using the right coping strategies among the students.